Pelatihan Pembuatan Sediaan Jamu untuk Pencegahan Penyakit pada Masyarakat di Desa Sumbersuko, Malang - Rudy Mardianto; Agung Permata; Misgiati Misgiati (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Herbal medicine is an ancestral heritage that has become an important part of Indonesian people's lives. The lack of public knowledge about how to utilize and process natural ingredients to produce quality herbal medicine is a major obstacle that requires educational intervention. This community service activity aims to increase the knowledge of village health cadres about the use and processing of safe and quality herbal medicine. The activity was carried out in Sumbersuko Village, Wagir District, Malang Regency on August 29, 2025, participants consisted of 15 village health cadres. Evaluation of the activity was carried out with a pre-test and post-test. The pre-test results showed a general understanding of herbal medicine, the category of good at 7%, sufficient 13%, and less than 80%. The benefits of herbal medicine for disease prevention, the category of good at 13%, sufficient 20%, and less than 67%. The process of making and safety of herbal medicine, the category of good at 13%, sufficient 27%, and less than 60%. After socialization, the results of the post-test showed a general understanding of herbal medicine in the category of good at 47%, sufficient 7%, and less than 47%. The benefits of herbal medicine for disease prevention were categorized as good at 67%, sufficient at 13%, and insufficient at 20%. The manufacturing process and safety of herbal medicine were categorized as good at 67%, sufficient at 7%, and insufficient at 27%. Thus, a structured outreach program has proven effective in increasing the knowledge of health cadres and has the potential to support the strengthening of the role of herbal medicine as a health alternative based on local wisdom.